Elucidating the ecological patterns of sympatric sea-bob shrimp species Xiphopenaeus dincao and X. kroyeri: A temporal and spatial approach - Jaconis, Milena Silva [UNESP] (2024)
We evaluated the abundance and spatio-temporal distribution of adult individuals of sympatric shrimp species, X. kroyeri and X. dincao, under the influence of environmental variables. The study period took place from July 2021 to June 2022 in Ubatuba Bay, southeastern coast of Brazil. Monthly sampling of specimen and environmental variables occurred using a shrimp fishing boat along four transects of different depths. The abundance peak was differential: X. dincao occurring in the autumn and X. kroyeri in the winter. There was spatial segregation between the species, with X. dincao predominating in more restricted and shallower habitats, while X. kroyeri showed higher abundance in deeper depths. Temporal differentiation of the highest abundance and the habitat partitioning between the species demonstrate different strategies in resource use, following a scenario that reduces competitive pressures and maintains coexistence stability. The closed fishing season appears to offer more protection for X. dincao. Although both periods do not cover the peak of X. kroyeri abundance, its abundance increased in the following months. Our findings describe the population and ecological characteristics of two sea-bob shrimp species, previously regarded as monotypic, and contribute to a deeper understanding of the actual status of these populations.